Empirical Study of Digital Poverty: A Case Study of a University of Technology in South Africa. (1st December 2016) - Manduna, Watson
Abstract: This research evaluates the availability and use of Information and Communications Technology (ICT) by students from disadvantaged and privileged families studying Computer Science at a University of Technology in South Africa. A questionnaire was distributed to a stratified random sample of 50 first-and 20 thirdyear students. Descriptive statistics were used to analyze and present the results of the study. The results suggested that a low level of education is associated with digitally poor people. Results of the research also proposed that men had more opportunities of using ICTs than women. The more economically poor a family was, the more digital poor it was. The research also showed that living in the rural areas seems to decrease the probability of being (more) digitalized. The results of the study were later used to create a framework for assessing the degree of ICT usage and to group the population into digital poverty levels.